At daddy's on Saturdays - Girard, Linda Walvoord; Friedman, Judith, 1945- (Niles, Ill. : A. Whitman, 1987)
Although her parents' divorce causes her to feel anger, concern, and sadness, Katie discovers that she can keep a loving relationship with her father even though he lives apart from her.
Elementary School Library Collection (Bro-Dart)
Booklist
3.0
K-3
Keywords: Divorce -- Fiction; Fathers and daughters -- Fiction; Divorce -- Fiction; Fathers and daughters -- Fiction